Budicí obvody výkonového tranzistoru SiC MOSFET - Vitek, Vojtech (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2013)
Bakalárska práca opisuje princípy budenia výkonových tranzistorov MOSFET z materiálu karbid kremíka SiC. Cieľom je podrobne opísať jednotlivé typy budenia a základné zásady pri navrhovaní budičov. Praktickou časťou práce je osadenie dosky plošných spojov budiča navrhnutého na UVEE FEKT VUT Brno a overenie jeho činnosti .

The bachelor thesis describes gate driving principles of power MOSFET transistors made of silicon carbide material. The autor's aim is describing a different types of gate drivers and basic rules during process of designing gate drivers. In the theoretical part, the author will mount printed circuit board of gate driver designed on UVEE FEKT VUT Brno and verify functionality.
Drivers for power SiC MOSFET transistors
Keywords: budič; tranzistor; MOSFET; karbid kremíka; gate driver; transistor; MOSFET; silicon carbide